Toward a Robust Plio‐Pleistocene Chronostratigraphy for ODP Site 762 - Gerald Auer; David De Vleeschouwer; Beth A. Christensen (Geophysical Research Letters)
Abstract The advent of rapidly acquired proxy records provides paleoceanographers and paleoclimatologists with a wealth of high‐resolution data. These data are a boon for the community, as they enable millennial or even submillennial scale interpretation of past climate and ocean change. Multisite and multiproxy research permits regional and global correlations with high precision. Yet, accuracy is sometimes lost sight of, resulting in inaccurate age constraints. To highlight the importance of chronostratigraphic accuracy, we examine a recent publication by Stuut et al. (2019, https://doi.org/10.1029/2019GL083035) that presents a chronostratigraphic framework potentially at odds with regional chronostratigraphy by up to 300 kyr in the Pliocene and 600 kyr in the Pleistocene. Using all available chronostratigraphic data, we provide an alternate integrated stratigraphic framework resulting in a higher degree of uniformity among regional climate archives and confirm the timing of a major climatic transition in Australia between ~3.55 and 3.3 Ma.